2013
DOI: 10.1038/bjc.2013.106
|View full text |Cite
|
Sign up to set email alerts
|

Competing mortality in patients diagnosed with bladder cancer: evidence of undertreatment in the elderly and female patients

Abstract: Background:Bladder cancer (BC) predominantly affects the elderly and is often the cause of death among patients with muscle-invasive disease. Clinicians lack quantitative estimates of competing mortality risks when considering treatments for BC. Our aim was to determine the bladder cancer-specific mortality (CSM) rate and other-cause mortality (OCM) rate for patients with newly diagnosed BC.Methods:Patients (n=3281) identified from a population-based cancer registry diagnosed between 1994 and 2009. Median foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(110 citation statements)
references
References 23 publications
(30 reference statements)
2
108
0
Order By: Relevance
“…[28][29][30] Published single-center series universally include patients who have undergone lymph node dissection in addition to RC; the higher long-term survival in these cohorts may reflect greater use of this surgical approach. 20,22,27 Elderly patients treated with RC were less likely than younger patients to receive ACT; only 5% of patients aged 80 years received ACT, as compared with 27% of those younger than 70 years. Those who did receive chemotherapy after the age of 70 years were less likely to receive cisplatin than younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] Published single-center series universally include patients who have undergone lymph node dissection in addition to RC; the higher long-term survival in these cohorts may reflect greater use of this surgical approach. 20,22,27 Elderly patients treated with RC were less likely than younger patients to receive ACT; only 5% of patients aged 80 years received ACT, as compared with 27% of those younger than 70 years. Those who did receive chemotherapy after the age of 70 years were less likely to receive cisplatin than younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…These factors are practically impossible to elucidate from retrospective databases. The small amount of information available is conflicting; treatment for all bladder cancer as recorded in the SEER database stratified into intravesical, systemic therapy or cystectomy has shown no difference by gender [32] and an English study of high-risk NMIBC noted that men and women were equally likely to receive Bacillus Calmette-Guérin (BCG) [33]. However, comparison of treatment of superficial cancers in a Spanish study found female patients were almost 5 times more likely to receive intravesical therapies after transurethral resection (TUR) compared with their male counterparts despite there being a greater proportion of men with G3pT1 tumors than women [20] (the difference was not explained by men opting for immediate cystectomy), and 2 American studies have indicated that a higher proportion of female patients receive radiotherapy for MIBC [22,31].…”
Section: Does Type Of Treatment Received Differ Between Genders?mentioning
confidence: 99%
“…Bladder cancer (BC) is a common malignancy of the urinary tract (1,2). Bone metastasis occurs in ~40% of patients with BC (3,4).…”
Section: Introductionmentioning
confidence: 99%